Pedagogical Mechanisms Of Ensuring Samaradorli, Teaching English Language (Eurasian Journal of Learning and Academic Teaching, 2023)
This article is about the modern pedagogical technologies and their effectiveness in educational system. Defectological system of teaching in disabled part of education. Field of higher pedagogical education, and the personnel training system for conducting educational work with children with mental and physical developmental disabilities.